Pemikiran dan Gerakan Pembaharuan Politik Islam Jamaluddin Al Afghani - Fatkhul Wahab; Zainuddin (LP3M IAI Al-Qolam Malang, 2022)
Jamaluddin Al Afghani is a true Islamic fighter, his whole life from when he was young until the end of his life was devoted to fighting for Muslims from the clutches of the invaders. According to Jamaluddin Al Afghani, the decline of Muslims is actually the result of Muslims themselves who have misunderstood the teachings of Islam, so that they really lag behind the Western world. In addition to the absence of a sense of unity and unity among Muslims themselves, not only among the common people but also among the ulama. The absence of communication and interaction between the ulama led to the breakdown of the ulama network which of course had an impact on the general public. Another factor is the absolute system of government that acts arbitrarily against its people, making the backwardness of Muslims worse. For Jamaluddin Al Afghani, a good and ideal government system is a republican or democratic government system, because this government system involves the people in making decisions through their representatives who sit in parliament. This democratic system of government is what the Qur'an actually wants, not the caliphate government system, where in this government, wisdom and authority are only in the hands of the caliph, and this allows violations of individual rights. Key words: Jamaluddin Al Afghani, Islam, politics, revolution, modernism.